ANALISIS PERBANDINGAN PENDANAAN ASET TETAP ALTERNATIF LEASING DENGAN PINJAMAN BANK DALAM EFISIENSI PAJAK PENGHASILAN BADAN (STUDI KASUS PADA PT CAHAYA GASDOM) - Wiwik Budiarti; Fadilah Dian Hidayati (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2015)
The amount of funds that must be prepared is the main reason for the company to chose an external source of funds to finance the procurement of its fixed assets. The fulfillment of funding requirements in the procurement of fixed assets can be done by way of lease (leasing) or by bank loans. Both of these funding sources to help companies without disrupting the operational activities of companies that need capital. This study aims to determine the differences present value cash outflow and how much the efficiency of the corporate income tax on fixed assets financing leasing aternatif with a bank loan in PT Cahaya Gasdom using primary and secondary data. The analytical method that used is a comparative analysis of the present value of cash outflow and efficiency of corporate income tax. Results of the study revealed the fact that (1) Present value cash outflow leasing alternative is less than the bank loans on depreciation using the straight-line method and depreciation using the declining balance method, the difference between the present value of the cash outflow amounted to Rp 46,819,503 and Rp 10,461 .410. (2) Tax savings alternative financing leasing is greater than the alternative of a bank loan, depreciation using the straight-line method and depreciation using the declining balance method, the difference in tax savings amounted to Rp 44,005,075 and Rp 5,771,872.Key words: Financing Fix Asset and Income Tax Efficiency